Titanium Dioxide Addition to Heat Polymerized Acrylic Resin Denture Base Effect on Staphylococcus aureus and Candida albicans - Dwi Tjahyaning Putranti; Afrina Fadilla (Indonesian Dental Association, 2018)
Introduction: Heat-polymerized acrylic resin is used to manufacture almost all denture bases. One of the disadvantages of acrylic resin is its porosity and surface roughness; food scraps attach easily. If the dentures are not cleaned, they become a place for microbial species development and cause denture stomatitis, with Staphylococcus aureus and Candida albicans as the major etiologic agents. Adding nanoparticles of titanium dioxide to heat-polymerized acrylic resin may provide antimicrobial activity to the acrylic resin base. Objectives: This study aimed to determine whether adding TiO2 nanoparticles to heat-polymerized acrylic resin denture base materials affected the amounts of Staphylococcus aureus and Candida albicans. Methods: The samples in this study used heat-polymerized acrylic resin without the addition of TiO2 nanoparticles and with the addition of 2%, 3%, and 4% TiO2 nanoparticles on test bar sizes of 10 mm × 10 mm × 1 mm. There were 48 total test samples: 24 of Staphylococcus aureus and 24 of Candida albicans. The obtained data were analyzed by a one-way ANOVA test. Results: The results showed that adding TiO2 nanoparticles influenced the amount of Staphylococcus aureus (p<0.05) and Candida albicans (p<0.05). A least significant difference test showed differences of effect in the amounts of Staphylococcus aureus when TiO2 concentrations of 2%, 3%, and 4% were added to heat-polymerized acrylic resin denture base and there were differences in effect to amounts of Candida albicans when TiO2 concentrations of 2%, 3%, and 4% were added to heat-polymerized acrylic resin denture base. Conclusion: Adding TiO2 nanoparticles to heat-polymerized acrylic resin denture base material affects the amounts of Staphylococcus aureus and Candida albicans.